Vol. 16, No. 15, April 24, 1964 (1964)
•Faculty Changes for Next Year •Melvin Belli Speaks Here •American Judicature Society to be Honored •Libel and Slander •Miscellaneous •At the Flicks •Ode to a Toad (or Ode to a 28 Credit Load